ANALISIS PENGARUH PENERAPAN INFORMASI AKUNTANSI MANAJEMEN TERHADAP KEBERHASILAN PERUSAHAAN JASA PEMBORONGAN SWASTA DI JAWA TIMUR - Setyadarma, Bambang (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2003)
The direction of this research there is for testing as empirical as much as of strong regression contribution about management accounting information's implementation, companies old, leaders status, an education with leaders experience or kindly about business job service companies for successful 's private jon service companies at East Java. Relevantion about about regresion contribution management accounting information's implementation togethers indicator-indicator for companies successful of private job service as empirical be able to verified's really, where management accounting information to own of factor more essential in decision making process specially about necessaries side comopanies management internal. The sample of research there is private companies middle class to high that stay at East Java area that doing operationals activity until 2002 years, 5 years minimum, to pass East Java Bina Marga Public Job Dines service of Area Office. Data analysis for this riser do it with using Analysis of Variance (F Test). This case to show analysis as clear that successful companies in regression model be able to estimate with good enough by support factor of succesful about it that is: an education and companies experience leader (best linear biased estimator).